Arbitration of Disputes Arising from the Implementation of International Public Procurements in the Algerian Law - Nouioua, Houda (Journal of Human Sciences, 2020)
The opening of arbitration of disputes arising from the implementation of international public procurements to public law entities is considered to be a significant change in the legal system in the resolution of disputes using alternative methods. This opening constitutes also a legal guarantee encouraging foreign operators to participate in public procurements concluded by the Algerian State with its various bodies in order to implement projects, especially major ones, with the aim of developing the national economy.